How would you apply the Method of Differences to solve this problem:

\(f(x)\) is a polynomial of degree 2 such that that

\[ f(1) | f(2), f(2) | f(3), f(3) | f(4). \]

Show that \( f(2) = \pm f(1) \).

No vote yet

17 votes

×

Problem Loading...

Note Loading...

Set Loading...

Easy Math Editor

`*italics*`

or`_italics_`

italics`**bold**`

or`__bold__`

boldNote: you must add a full line of space before and after lists for them to show up correctlyparagraph 1

paragraph 2

`[example link](https://brilliant.org)`

`> This is a quote`

Remember to wrap math in \( ... \) or \[ ... \] to ensure proper formatting.`2 \times 3`

`2^{34}`

`a_{i-1}`

`\frac{2}{3}`

`\sqrt{2}`

`\sum_{i=1}^3`

`\sin \theta`

`\boxed{123}`

## Comments

Sort by:

TopNewestLet \(g(n)=f(n+1)-f(n), h(n)=g(n+1)-g(n)\). Then g is a polynomial of degree 1, and h is a polynomial of degree 0, i.e. a constant.

Clearly from the given condition, \(f(2)|g(2)\) and \(f(3)|g(3)\). Hence \(f(2)|g(3)\), so \(f(2)|h(2)\). But \(h(1)=h(2)\), so \(f(2)|h(1)=g(2)-g(1)\), so \(f(2)|g(1)=f(2)-f(1)\), so \(f(2)|f(1)\).

Since \(f(1)\) and \(f(2)\) divide each other, they must have the same absolute value, which was what we wanted.

Log in to reply

That's a great solution. I tried expressing \(f(2)\) as some factor times \(f(1)\) and \(f(3)\) as some factor times \(f(2)\), but I just got a big mess.

Log in to reply

You can see how knowing the "method of differences" makes this proof seem almost immediate / obvious.

I would encourage you to work through your "big mess", especially in light of Ang's solution above. Use your notation to work through, see how it follows through, and why you weren't able to push through.

Log in to reply

Let \(f(2) = a \cdot f(1), f(3) = b \cdot f(2), f(4) = c \cdot f(3).\) Then using simple algebra, I obtain

\[ \begin{cases} D_2(1) = f(1) \cdot (ab -2a +1), \\ D_2(2) = f(1) \cdot (abc -2ab+a). \end{cases} \]

As \(D_2(n)\) is constant for all \(n\), those two expressions are the same:

\[ f(1) \cdot (ab -2a +1) = f(1) \cdot (abc -2ab+a). \]

Division by \( a \cdot f(1) \) is allowed, as the conditions imply \( a,f(1) \not = 0\):

\[ b-2 + \frac{1}{a} = bc - 2b +1. \]

The right hand side is an integer, so the left hand side is too: this implies \( \frac{1}{a}\) is an integer as well, so \(a\in \{ -1,1 \}\).

Log in to reply

However, why do you say that "the conditions imply \(a, f(1) \neq 0\)"? How do the conditions imply that? Why can't either of them be 0?

Log in to reply

Log in to reply

In particular, Does \( 0 \mid k \) or \( k \mid 0\) ?

Log in to reply

For the sake of contradiction, let's assume that \(f(1) = 0\). Then \(f(1) \mid f(2) \implies f(2) = 0\), because for every integer \(a\), \(a \cdot 0 = 0\). Similarly, \(f(2) \mid f(3) \implies f(3) = 0\). So, \(f(1)=f(2)=f(3)=0\). But \(f(x)\) is a second degree polynomial, so that is impossible. Therefore, the assumption that \(f(1)=0\) was wrong, so \(f(1) \not = 0\). Using a similar argument (if I assume that \(f(2)=0\)), \(f(2) \mid f(3) \implies f(3) = 0\) and \(f(3) \mid f(4) \implies f(4) = 0\), which is not possible due to the degree of \(f(x)\), so \(f(2) \not = 0\). Finally, assuming \(a=0\), \(f(2) = a \cdot f(1) \implies f(2)=0\), but \(f(2) \not = 0\), so \(a \not = 0\).

I have made an assumption here: if \(f(x)\) is a second degree polynomial, then \(f(1)=f(2)=f(3)=0\) is impossible. That is because \(D_1(1)=f(2)-f(1)=0\) and \(D_1(2)=f(3)-f(2)=0\), implying \(D_2(1)=D_1(2)-D_1(1)=0\). But as \(f(x)\) is a second degree polynomial, \(D_2(x)\) is \(2! = 2\) times the leading coefficient of f(x), so that leading coefficient is \(0\). But a polynomial can't have a leading coefficient of \(0\), so the assumption that \(f(1)=f(2)=f(3)\) was false.

I could also have proved this by using the fact that a \(k\)-th degree polynomial has exactly \(k\) (complex) roots, but it was nice that the Method of Differences could prove this as well.

Log in to reply

At this point, you should also question "Why did I need to deal with all of this, when Ang didn't?"

Hint:\( a \mid 1 \Rightarrow a = \pm 1 \).Log in to reply

I do not understand this notation. What do you mean by that?

Log in to reply

I believe he is using the "divides" notation. That is, \( a|b \iff \exists k \in \mathbb{Z} : ak = b \)

Log in to reply

For someone not knowing that notation, your notation isn't really going to help, I'm afraid… ;-)

Log in to reply

Log in to reply

Log in to reply

Log in to reply

We would love more awesome articles such as this..

Log in to reply